2008
DOI: 10.1016/j.metabol.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress precedes the onset of high-fat diet–induced insulin resistance and obesity

Abstract: Running title: oxidative stress induced by high-fat diet Key words: insulin resistance, oxidative stress, β-oxidation, NADPH oxidase Reprint requests to corresponding author. 1The abbreviations used are the following: HFD, high-fat diet; ROS, reactive oxygen species; PPARα, peroxisome proliferator-activated receptor-α; Nox, NADPH oxidase; FFAs, free fatty acids; Acox, acyl-CoA oxidase; CPT-1a, carnitine palmitoyltransferase 1a; CYP2E1, cytochrome P450 2E1; GTT, glucose tolerance test; Gpx, glutathione peroxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
331
3
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(373 citation statements)
references
References 25 publications
32
331
3
7
Order By: Relevance
“…The second involves a priori increased NADPH oxidase activity in the placenta of obese women. In fact, NADPH oxidase appears to be the major contributor of ROS production in non-pregnant obese women [8,25,26]. Our findings differ from those earlier reported by Roberts et al [27] who found no direct relationship between lean, overweight, and obese BMI classes and oxidative stress [27].…”
Section: Discussioncontrasting
confidence: 89%
“…The second involves a priori increased NADPH oxidase activity in the placenta of obese women. In fact, NADPH oxidase appears to be the major contributor of ROS production in non-pregnant obese women [8,25,26]. Our findings differ from those earlier reported by Roberts et al [27] who found no direct relationship between lean, overweight, and obese BMI classes and oxidative stress [27].…”
Section: Discussioncontrasting
confidence: 89%
“…The different timing of high cholesterol diet supply, either continuous or alternate, has a significant impact on HDL concentration level (about double in IHF, compared to HF cases), on Total Cholesterol/HDL ratio (more than double in HF compared to IHF group) as well as on TG concentration, significantly lower in IHF group. The amount of circulating LDL is reflected by a higher plasma concentration of oxLDL, with about sixfold increase compared to controls [37]. The same hypercholesterolemic plasma environment accounts for an increased expression of Apolipoprotein A1, especially in HF group, as previously reported [38] [39].…”
Section: Circulatory Lipid/lipoproteins and Inflammatory Markerssupporting
confidence: 63%
“…In animal studies, rats fed a high-sugar/high-fat diet had increased lipid peroxidation in the brain (Ribeiro et al, 2009, Stranahan et al, 2011, elevated plasma malondialdehyde (MDA) concentrations (a marker of lipid peroxidation) (Panchal et al, 2011) and increased mRNA expression levels of genes involved in ROS production in both the liver and adipose tissue (Matsuzawa-Nagata et al, 2008). In obese adults with metabolic syndrome, reducing energy intake by 2000kJ, mainly via carbohydrate restriction, was associated with decreased oxidative stress and increased levels of antioxidant markers, alpha-tocopherol and ceruloplasmin (Skalicky et al, 2009).…”
Section: Diet and Its Effect On Oxidative Stressmentioning
confidence: 99%